2017
DOI: 10.1111/cen.13411
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional association of coffee and caffeine consumption with sex hormone‐binding globulin in healthy nondiabetic women

Abstract: Consumption of high coffee and caffeine is associated with a reduced risk of low SHBG, an established risk marker for T2DM, which might contribute to the protective effects of coffee for type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…In a study among 1563 Norwegian men, coffee was positively associated with SHBG and total testosterone levels [ 48 ]. A recent French study in 2377 women reported that (caffeinated) coffee, but not tea intake, was positively related with SHBG levels, notably in postmenopausal women [ 49 ], confirming earlier studies on coffee and SHBG levels in women. Low SHBG levels are considered as a consistent marker of type 2 diabetes risk, especially in women [ 50 ].…”
Section: Discussionsupporting
confidence: 78%
“…In a study among 1563 Norwegian men, coffee was positively associated with SHBG and total testosterone levels [ 48 ]. A recent French study in 2377 women reported that (caffeinated) coffee, but not tea intake, was positively related with SHBG levels, notably in postmenopausal women [ 49 ], confirming earlier studies on coffee and SHBG levels in women. Low SHBG levels are considered as a consistent marker of type 2 diabetes risk, especially in women [ 50 ].…”
Section: Discussionsupporting
confidence: 78%
“…However, no relation was observed with caffeinated coffee and sex hormones (93). Similar results were also reported in a cross-sectional study with 2377 women (100). Nonselective blocking of adenosine receptors by caffeine, chlorogenic acid, and other phytochemicals, resulted in enhanced intracellular concentration of cyclic AMP.…”
Section: Q4: Does Coffee Consumption Affect Menopause Time?supporting
confidence: 82%
“…[ 1 ] Hepatic SHBG production is regulated by nutritional factors. [ 20–22 ] Since there are epidemiological evidences showing a positive relationship between coffee and caffeine consumption and SHBG plasma levels [ 26,27 ] we decided to test whether caffeine consumption could increase SHBG production and the related underlying molecular mechanisms. Our results using HepG2 cells showed that caffeine did not increase SHBG production in in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported a clear correlation between caffeine and SHBG levels. [ 26,27 ] We therefore decided to explore whether caffeine could affect SHBG production in vivo. To do so we used a humanized SHBG transgenic mice, which have been extensively used to determine the mechanisms regulating SHBG in vivo since regular mice do not express SHBG gene in their livers and do not have SHBG in their blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation